Analisis Strategi Promosi @Jurnalrisa Coffee Di Masa Pandemi Covid-19 Di Media Sosial Instagram - Ike Herliana Ginting; Ratih Hasanah Sudrajat (Jurnal Ilmiah Wahana Pendidikan, 2022)
The presence of the Covid 19 pandemic in Indonesia has now greatly affected many sectors, starting from health, politics, education and the economy, which has harmed many people. Even the business sector which has fallen drastically, one of which has been affected by this pandemic is the food and beverage business. From this condition, there is a lot of competition in this business sector which is getting tougher. Therefore, the purpose of this study is to analyze the promotional strategy carried out by Jurnal Risa Coffee in advancing sales during the Covid 19 pandemic through Instagram social media. This study uses the theory of Promotion Strategy, Promotional Mix, Instagram Social Media. The method used in this research is descriptive qualitative approach with observation and in-depth interviews. The results obtained from this study are that Jurnal Risa Coffee has carried out its promotional strategy by implementing promotional stages that optimize marketing. Then include the promotion mix, Advertising through the concept of an ad copy strategy, sales promotion which focuses on the current pandemic conditions, namely sterilization of products by giving vouchers, Direct Marketing through Instagram Social Media, and Personal Selling through Instagram face to face.